Taroba elephantina: a new genus and species of Hapithinae cricket from southern Brazil (Orthoptera, Grylloidea, Podoscirtidae). - Dias, Pedro G.B.S.; Mello, Francisco de Assis Ganeo de [UNESP] (Pensoft Publishers, 2010)
A new genus and species of cricket belonging to the Hapithinae: Neomorphini (Podoscirtidae) is described from the forests of the Iguacu National Park, State of Parana, Brazil. The new genus is thoroughly compared with Neomorpha Desutter, 1987, the only other member of the Neomorphini described so far.